State, society, and minorities in South and Southeast Asia - Kukreja, Sunil (Lexington Books, 2015)
"This book provides a multidisciplinary and multilayered assessment of the salience of the ethnic and religious realities of shaping various South and Southeast Asian nations. Featuring chapters on Afghanistan, Bangladesh, India, Sri Lanka, Cambodia, Thailand, Malaysia, and Indonesia, it offers a deep appreciation of the challenges that these societies confront in integrating and/or responding to specific ethnic- and/or religious-based conflicts and tensions"--Provided by publisher